Follicular wave development, oestrus interval and ovulation rate in timed-artificial inseminated Kedah-Kelantan, brakmas, charoke and crossbred cows - Amri, Azizah (2013)
The demands for beef, goat meat and mutton have been increased every year, and presently the national requirements for beef, goat meat and mutton are largely met by imports. Thus, steps should be taken to propagate the number of animals to reduce the loss in revenue through importation bills. The objectives of the study therefore were to (i) determine the differences in follicular wave development, (ii) determine the relationship and effect of ovarian follicular waves pattern on oestrus interval, ovulation time and pregnancy rate at observed oestrus, (iii) determine the oestrus interval and pregnancy rate at observed oestrus and (iv) develop the TAI and determine efficiency of frequency of TAI (single or dual) on the pregnancy rate of Kedah-Kelantan (KK), Brakmas (BK), Charoke (CK) and crossbred cattle following controlled internal drug release (CIDR) and prostaglandin (PGF) treatments. The hypothesis of the study is TAI at right ovulation will result in higher conception and/or pregnancy rates then AI of observed oestrus (a.m.-p.m. rules). All experiments used a single synchronisation protocol where cows were inserted with CIDR® containing 1.38 g progesterone (P4) for 7 days and given a intramuscular injection a synthetic PGF analogue of 25 mg PGF (Estrumate®, Schering – Plough Animal Health, Australia) two days prior to CIDR removal. Both ovaries of thirty cows comprised of Kedah-Kelantan (KK) and its crosses, Brakmas (BK) and Charoke (CK) were examined with a portable ultrasound machine at 6 hours interval in one duration of oestrous cycle to determine follicular development (FD). A total of 35 KK and its crosses were used to determine the interval between removal of CIDR® to oestrus and ovulation, AI and pregnancy diagnosis (PD) at the observed oestrus. The oestrous behaviour was observed for 72 hours at two-hour intervals beginning 12 hours after CIDR® removal, and AI was carried out at 6 and 12 hours after oestrus was observed. In another study, 64 KK cattle and its crosses were used to estimate ovulation time, and 60 KK cattle and its crosses cows were used to determine the TAI based on the ovulation time obtained. The mean diameter of dominant ovulatory follicles after CIDR removal was 11.73 ± 0.07 mm, and newly developed follicles after ovulation emerged at 1.37 ± 0.16 days with a mean size of 5.1 ± 0.02 mm. The number of follicles at emergence was significantly higher in KK (4.4±0.63, P=0.036) compared to BK (3.2±0.36) and CK (2.6±0.37). The mean interval from removal of CIDR to oestrus and ovulation, and oestrous to ovulation were 52.97 ± 6.16 h, 94.42 ± 16.41 h and 53.75 ± 25.36 h, respectively. The pregnancy rate (PR) of observed oestrus was higher in CK (43.8%), followed by KK (31.3%) and BK (25%). The mean estimation time of ovulation of the four breed groups was 85.1±1.6 h (P=0.467) calculated from the removal of CIDR®. The proportion of animals pregnant was higher with AI at 56 h groups with percentage pregnancy of 20% followed by AI at 72 h (15%) and AI at 65 h (10%) groups. The single AI has produced a pregnant of a proportion 25% compared 20% for the dual AI method. The results of the present study has found the follicular growth which followed a wave like pattern, and there were differences in the development of the first, second and third follicular wave (FW) in BK, CK and KK cattle. There was a tendency for second and third dominant follicles to emerge at the same time, and both competed with each other to develop. The DF‟s whose its granulose cells produce enough oestradiol concentrations would enhance the development of the luteinising hormone (LH) receptors for higher LH production to induce ovulation. The study provided additional knowledge on the oestrous synchronization of KK, BK, CK and crossbred cattle for TAI. In conclusion, due to the results of proportion of cows pregnant, the study has not agreed with the hypothesis that TAI at right ovulation will result in higher conception rates then AI of observed oestrus (a.m.-p.m. rules). However, it was suggested the oestrous synchronisation for TAI in present study rendered further refinement, adjustment and modification in order to obtain a higher result in a conception or pregnancy rate.